2000
DOI: 10.1046/j.1365-3148.2000.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of premedication guidelines and leukoreduction on the rate of febrile nonhaemolytic platelet transfusion reactions

Abstract: Platelet transfusion reactions were prospectively studied in haematology/oncology patients at five university teaching hospitals over three consecutive summers. The initial summer study provided baseline information on the use of premedications and the rate of platelet transfusion reactions (fever, chills, rigors and hives). Most (73%) platelet recipients were premedicated and 30% (95% CI 28-33%) of transfusions were complicated by reactions. The second study followed implementation of guidelines for premedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 12 publications
2
77
1
10
Order By: Relevance
“…Soluble factors in the supernatant may be pyrogenic, including cytokines released during storage, particularly at room temperature [49,50]. Lin et al [51] demonstrated higher levels of IL-6 and -8 in post-red cell patients, including baseline IL-6 levels in cases vs controls, although cytokine levels did not vary accordingly in transfused products.…”
Section: Non-haemolytic Immunological Response To Transfusionmentioning
confidence: 99%
“…Soluble factors in the supernatant may be pyrogenic, including cytokines released during storage, particularly at room temperature [49,50]. Lin et al [51] demonstrated higher levels of IL-6 and -8 in post-red cell patients, including baseline IL-6 levels in cases vs controls, although cytokine levels did not vary accordingly in transfused products.…”
Section: Non-haemolytic Immunological Response To Transfusionmentioning
confidence: 99%
“…Many other actual or potential benefits of LR have been described. These include: reduced febrile nonhemolytic transfusion reactions; 92,93 alloimmunization to HLA and other antigens, …”
Section: Prevention Of CMV Transmission Through Transfusionmentioning
confidence: 99%
“…Allergic transfusion reaction is one of the two most common forms of transfusion reaction, the other being febrile non-hemolytic transfusion reactions (Ezidiegwu et al, 2004;Patterson et al, 2000). Allergic transfusion reaction is classified as mild or severe based on the symptoms that develop within several hours of transfusion, mild allergic reactions cause erythematous circumscribed lesions, with or without pruritus while severe allergic reactions (anaphylaxis) causes systemic symptoms of dyspnoea, wheezing, hypotension, tachycardia, loss of consciousness, shock, and in rare cases death (Tobian et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For their prevention anti-inflammatory drugs with pre-transfusion medication are used, with its efficacy and safety in question (Martí-Carvajal et al, 2010). Three kinds of drugs are commonly used for this pre-transfusion medication, either alone or in combination (Patterson et al, 2000). United States Physicians use acetaminophen and diphenhydramine as effective therapies for fever and allergy, respectively (Geiger and Howard, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation